Purposeful Program Theory: Effective Use of Theories of Change and Logic Models - and Funnell, Sue C.; Rogers, Patricia J. (Wiley, 2011)
Between good intentions and great results lies a program theory—not just a list of tasks but a vision of what needs to happen, and how. Now widely used in government and not-for-profit organizations, program theory provides a coherent picture of how change occurs and how to improve performance. Purposeful Program Theory shows how to develop, represent, and use program theory thoughtfully and strategically to suit your particular situation, drawing on the fifty-year history of program theory and the authors' experiences over more than twenty-five years."From needs assessment to intervention design, from implementation to outcomes evaluation, from policy formulation to policy execution and evaluation, program theory is paramount. But until now no book has examined these multiple uses of program theory in a comprehensive, understandable, and integrated way. This promises to be a breakthrough book, valuable to practitioners, program designers, evaluators, policy analysts, funders, and scholars who care about understanding why an intervention works or doesn't work." —Michael Quinn Patton, author, Utilization-Focused Evaluation"Finally, the definitive guide to evaluation using program theory! Far from the narrow 'one true way' approaches to program theory, this book provides numerous practical options for applying program theory to fulfill different purposes and constraints, and guides the reader through the sound critical thinking required to select from among the options. The tour de force of the history and use of program theory is a truly global view, with examples from around the world and across the full range of content domains. A must-have for any serious evaluator." —E. Jane Davidson, PhD, Real Evaluation Ltd.Companion Web site: josseybass.com/go/funnellrogers